2020
DOI: 10.1111/bpa.12873
|View full text |Cite
|
Sign up to set email alerts
|

A Zika virus primary isolate induces neuroinflammation, compromises the blood‐brain barrier and upregulates CXCL12 in adult macaques

Abstract: Zika virus (ZIKV) is a flavivirus that can cause neuropathogenesis in adults and fetal neurologic malformation following the infection of pregnant women. We used a nonhuman primate model, the Indian‐origin Rhesus macaque (IRM), to gain insight into virus‐associated hallmarks of ZIKV‐induced adult neuropathology. We find that the virus causes prevalent acute and chronic neuroinflammation and chronic disruption of the blood‐brain barrier (BBB) in adult animals. ZIKV infection resulted in specific short‐ and long… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 55 publications
1
8
1
Order By: Relevance
“…RNAemia at any other time points up to the day of necropsy was not observed in any of the pregnant dams. This differs from the reports in pregnant macaques where prolonged or re-emergent viremia for several weeks up to 70 dpi has been widely reported [ 24 , 25 , 28 30 , 41 , 43 , 55 ]. While prolonged viremia (46 to 53 days) has been reported in pregnant women [ 56 59 ], this appears to be uncommon.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…RNAemia at any other time points up to the day of necropsy was not observed in any of the pregnant dams. This differs from the reports in pregnant macaques where prolonged or re-emergent viremia for several weeks up to 70 dpi has been widely reported [ 24 , 25 , 28 30 , 41 , 43 , 55 ]. While prolonged viremia (46 to 53 days) has been reported in pregnant women [ 56 59 ], this appears to be uncommon.…”
Section: Discussioncontrasting
confidence: 99%
“…for several weeks up to 70 dpi has been widely reported [24,25,[28][29][30]41,43,55]. While prolonged viremia (46 to 53 days) has been reported in pregnant women [56][57][58][59], this appears to be uncommon.…”
Section: Plos Pathogensmentioning
confidence: 97%
“…Here, long-term increased levels of C-X-C motif chemokine ligand 12 (CXCL12), which is a chemokine involved in lymphocyte trafficking and neural repair, were described. Additionally, the authors observed inflammation in the perivascular space and meninges, accompanied by lymphocytic infiltrations (147). This was also reported in fetal human brains, where an infiltration of T and B cells was observed in the perivascular space during ZIKV infection (Figure 2) (113).…”
Section: Zika Virus (Zikv)supporting
confidence: 56%
“…In order to penetrate the CNS, ZIKV must cross the BBB. ZIKV infection induces BBB disruption in the later stages of the disease ( Leda et al, 2019 ), as evidenced by fibrinogen diffusion into the CNS parenchyma ( Panganiban et al, 2020 ) and neuroinvasion of infected monocytes ( Ayala-Nunez et al, 2019 ; de Carvalho et al, 2019 ). However, during early ZIKV infection stages, the BBB remains intact.…”
Section: Introductionmentioning
confidence: 99%